2015
DOI: 10.1155/2015/470589
|View full text |Cite
|
Sign up to set email alerts
|

Microinflammation Factors in the Common Diseases of the Heart and Kidneys

Abstract: Aim. To determine levels of interleukin-8 (IL-8) and plasminogen activator inhibitor-1 (PAI-1) in different cardiorenal syndrome (CRS) modalities and to compare findings to some already investigated direct and indirect parameters of inflammation and atherosclerosis. Materials and Methods. Testing involved 114 examinees, divided into control and clinical groups suffering from different modalities and were formed according to the basis of a valid classification for CRS. Results. C-reactive protein (CRP) was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There is evidence that cognitive decline occurs in great apes. 9,10,139,252 In aged chimpanzees and orangutans, only certain types of tasks were affected—such as social cognition, some motor skills, and, in the case of orangutans and gorillas, relative numerousness judgment.…”
Section: Nervous System Disordersmentioning
confidence: 99%
“…There is evidence that cognitive decline occurs in great apes. 9,10,139,252 In aged chimpanzees and orangutans, only certain types of tasks were affected—such as social cognition, some motor skills, and, in the case of orangutans and gorillas, relative numerousness judgment.…”
Section: Nervous System Disordersmentioning
confidence: 99%
“…Decrease of glomerular filtration rate (GFR) increases the level of molecules which are markers of hemostasis. In addition, impaired renal function contributes to the formation of prothrombotic condition indirectly through the electrolyte disturbances and acid-base status influencing the change of activity of the enzyme coagulation [11]. It was found that atherosclerosis and risk of cardiovascular disease are associated with inflammation and procoagulant state.…”
Section: Fybrinolitic System and Kidney Diseasementioning
confidence: 99%
“…Today, it is considered that IL-8 also has an indirect role in the processes of renal fibrogenesis (Lane, 2013). Clinical studies in dialysis patients have shown that IL-8 plays the role of a predictor for cardiovascular events (Tasic et al, 2015;Nymo et al, 2017). PAI-1 is synthesized as a single-chain glycopeptide and is deposited in the platelets in a latent form, from which it is released on their activation.…”
Section: Introductionmentioning
confidence: 99%